Mathematical Narrations and Poetry. A Mathematical Resilience Tool - Cándida Filgueira Arias; Maria del Carmen Escribano Ródenas (Ignatianum University Press, 2022)
Mathematics frequently appear in stories, poetry, stories, literary narratives, in general in different literary genres. Numbers and Mathematics usually appear in the stories, poems and narratives of children's and youth literature. Likewise, in these literary genres spatial relationships, shapes, sizes, quantities, numbers are verified, and it is that in Mathematics the pillars of logic and creativity underlie (Cervera, 1983). Thus, it is intended to develop an analysis and reflection through a bibliographic review of children's and youth literature related to Mathematics as a resilient tool for coping with the teaching of this discipline, creating new learning situations to develop significant links between literature. "mathematics" and resilience.  The results of the research have revealed theoretical and practical tools (stories, tales, poetry, literary narratives, stories) that will accompany and promote resilient mathematical processes through the construction of symbolic spaces of refuge and socio-emotional acceptance through reading and creative expression motivated by children's and youth literature.   Las Matemáticas aparecen frecuentemente en cuentos, poesías, relatos, narraciones literarias, en general en distintos géneros literarios. Los números y las Matemáticas aparecen habitualmente en los cuentos, poemas y narraciones de la literatura infantil y juvenil. Así mismo, en estos géneros literarios se constatan relaciones espaciales, formas, tamaños, cantidades, números, y es que en las "Matemáticas subyacen los pilares de la lógica y la creatividad" (Cervera, 1983, p. 32). Así pues, se pretende desarrollar un análisis y reflexión a través de una revisión bibliográfica de la literatura infantil y juvenil relacionada con las "Matemáticas como herramienta resiliente para el afrontamiento de la enseñanza de esta disciplina creando nuevas situaciones de aprendizaje para desarrollar vínculos significativos entre la literatura matemática y la resiliencia" (Cervera, 1983, p. 22). Los resultados de la investigación han dado a conocer herramientas teóricas y prácticas (relatos, cuentos, poesías, narraciones literarias, relatos) que acompañarán y favorecerán los procesos resilientes matemáticos a través de "la construcción de espacios simbólicos de refugio y acogimiento socioemocional mediante la lectura y la expresión creativa motivada por la literatura infantil y juvenil" (Pavón, 2015, p. 15)